Outcome of Bacterial Sepsis in Neonate with Determination of Pathogens and Their Antimicrobial Susceptibility - Ferdous, Navila; Mannan, Md Abdul; Yasmin, Sabina; Shahnewaz, Abdullah Al; Khan, Masuma; Anwar, Parves (Bangladesh Critical Care Journal, 2021)
Background: Sepsis in neonate remains a significant cause of mortality and morbidity in developing countries. Neonatal sepsis requires accurate and timely clinical and laboratory diagnosis and proper management for better outcome. In this study an attempt has been made to know the positivity rate of neonatal sepsis, identify the bacterial isolates responsible for EOS and LOS and determine their sensitivity pattern to various antimicrobial agents, and outcome of neonatal sepsis. Methods: A cross sectional descriptive single-centre study was conducted on neonates , over a period of 12 months. Essential investigations were sent by collecting samples under aseptic precautions. Empirical antimicrobial therapy was started according to antimicrobial guidelines in this NICU. Results: Out of 1423 screened blood cultures 13.49% reported as positive and EOS and LOS accounted for 33.85% and 66.15% of cases respectively. Over half (52.60%) of neonates had sepsis with gram negative bacteria and 47.40% with gram positive bacteria and ratio was 1.1:1. Common organisms were Coagulase-Negative Staphylococci-CONS (42.19%), Acinetobacter (22.40%),Enterobacter (18.75%).Total mortality rate was 6.96% & death rate was 23.96% in culture proven sepsis & 04.31% in culture negative isolates (p-value: <0.00001). In culture-proven sepsis the mortality rate 30.71% & 10.77% (P-value: 0.00219) in LOS & EOS; and 30.69% &16.48% (p-value: 0.02126) in gram positive & gram negative sepsis respectively. Acinetobacter (44.19%) showed higher death rate followed by MRSA (33.33%), E.Coli (33.33%). In EOS, gram positive & gram negative bacteria accounted for 55.38% & 44.62%; and in LOS, 43.31% & 56.69% respectively. CONS (50.77%), the commonest followed by Acinetobacter (18.46%) and Enterobacter (13.85%) in EOS. In LOS, CONS (37.80%) was the most isolated prevalent organism followed by Acinetobacter (24.41%) and Enterobacter (21.26%). Gram positive organisms showed higher level of sensitivity to Vancomycin (91%), Linezolid (90%), Netilmicin (65%). Among the Staphylococci (Coagulase negative & positive), around 86% were resistant to Cloxacillin/Methicillin. Gram negative bacteria had best susceptibilities to Colistin (74%) & Polymyxin-B (70%) than Cotrimoxazole (51%), Netilmicin (32%), Ciprofloxacin (32%), Piperacillin+ Tazobactem (27%), and Levofloxacin (24%). Among the commonly used antibiotics, the susceptibilities were remarkably low to Ampicillin (5.73%), Gentamicin (26.04%), Amikacin (11.46%), Ceftazidime (4.69%), Cefepime (2.08%) in comparison to Ciprofloxacin (31.25%), Imipenem/Meropenem (35.42%) & Netilmicin (47.92%) for both gram positive & negative isolates. Conclusion: Present study indicated that more mortality observed in culture-proven sepsis especially in gram negative sepsis. CONS continue to be the predominant causative organism in both EOS and LOS followed by Acinetobacter, Enterobacter. The antibiotic susceptibility profile suggested that for a given cohort empiric Netilmicin- Imipenem / Vacomycin or Netilmicin- Ciprofloxacin / Vancomycin initial choice where patient can not improve with initial empiric antimicrobial therapy (Ampicillin and Gentamicin) in EOS before blood culture reports are available or can considered be for initial empiric therapy in LOS. Early intervention with evidence based unit specific empiric chemotherapy before availability of culture reports that will improve outcome of neonate with sepsis and can reduce the morbidity and mortality as well. Bangladesh Crit Care J September 2021; 9 (2): 79-86